Association between D-dimer to lymphocyte ratio and in hospital all-cause mortality in elderly patients with sepsis: a cohort of 1123 patients - Long, Xinguang; Hu, Zhenkui; Song, Chao; Zhang, Jinhui (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe D-dimer to lymphocyte ratio (DLR), a novel inflammatory biomarker, had been shown to be related to adverse outcomes in patients with various diseases. However, there was limited research on the relationship between the DLR and adverse outcomes in patients with infectious diseases, particularly those with sepsis. Therefore, this study aimed to explore the association between the DLR and in hospital all-cause mortality in elderly patients with sepsis.MethodsA total of 1123 patients admitted in intensive care unit (ICU) were included in this study. The patients were categorized into quartiles (Q1-Q4) based on their DLR values. The primary outcomes included hospital mortality and ICU mortality. Kaplan-Meier analysis was conducted to compare all-cause mortality among the four DLR groups. The association between DLR and all-cause mortality in patients with sepsis was further elucidated using the receiver operating characteristic (ROC) curve and Cox proportional hazards regression analysis.ResultsThe study included participants with a median age of 75 (65-84) years, with 707 (63.0%) being male. The rates of hospital mortality and ICU mortality were 33.7% and 31.9%, respectively. Kaplan-Meier analysis highlighted a significantly increased risk of all-cause mortality among patients with elevated DLR values (log-rank p < 0.001). ROC curve analyses revealed that DLR had a stronger ability to predict hospital mortality and ICU mortality in patients with sepsis than D-dimer or Lym. Multivariable Cox proportional hazards analyses revealed DLR as an independent predictor of hospital death [per 1 SD increase in DLR: HR (95% CI): 1.098 (1.020-1.181); p = 0.013] and ICU death [per 1 SD increase in DLR: HR (95% CI): 1.095 (1.017-1.180); p = 0.017] during the hospital stay.ConclusionsA higher DLR value was associated with hospital and ICU all-cause death in elderly patients with sepsis. This finding demonstrated that the DLR could be a convenient and useful prognostic marker for sepsis prognosis.